2018
DOI: 10.1182/blood-2018-99-114344
|View full text |Cite
|
Sign up to set email alerts
|

High PARP-1 expression Predicts Poor Survival in Acute Myeloid Leukemia and PARP-1 Inhibitor and SAHA-Bendamustine Hybrid Inhibitor Combination Treatment Synergistically Enhances Anti-Tumor Effects

Abstract: PARP-1 plays a critical role in DNA damage repair and contributes to progression of cancer. To address the role of PARP-1 in AML, we analyzed the expression of PARP-1 in acute myeloid leukemia (AML) using RT-PCR. We found high expressers had higher levels of blast cells in bone marrow (P=0.003) and WBC in peripheral blood (P=0.008) and were associated with a more frequent FLT3-ITD mutation (28.2% vs 17.3%, P= 0.031). The overall survival (OS) and event free survival (EFS) of the high expression group were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The latest data also confirm that PARP1 was highly expressed in cytogenetically normal AML patients and AML cell lines compared to normal bone marrow cells. It may indicate that PARP1 plays a critical role in the development of AML [4]. Research by Fonfria et al [35] confirms the hypothesis that PARP enzyme activity is a central component of the pathway linking oxidative stress with TRPM2 activation [35].…”
Section: Discussionmentioning
confidence: 84%
“…The latest data also confirm that PARP1 was highly expressed in cytogenetically normal AML patients and AML cell lines compared to normal bone marrow cells. It may indicate that PARP1 plays a critical role in the development of AML [4]. Research by Fonfria et al [35] confirms the hypothesis that PARP enzyme activity is a central component of the pathway linking oxidative stress with TRPM2 activation [35].…”
Section: Discussionmentioning
confidence: 84%
“…Patients with higher PARP1 mRNA levels had a better response to 5-azacytidine and longer median survival after treatment initiation, suggesting that PARP1 can potentially serve as a guide to therapeutic decisions [119]. However, it exhibits an inverse correlation with prognosis in AML [120]. Other factors, such as ATM, XRCC6, and Lig IV, are also overexpressed in MDS patients as a consequence of some functional polymorphisms in their germlines [121,122].…”
Section: Mdsmentioning
confidence: 99%
“…We observed both an increase in H2AX signal and sensitivity of the cells with a combination of a PARPi and romidepsin compared to that of the individual agents alone (Figure 7C). The romidepsin effect on R-loops could explain multiple studies that have reported increased efficacy combining PARP1 inhibitors with romidepsin (65,66).…”
Section: Discussionmentioning
confidence: 99%